2024
DOI: 10.1136/tsaco-2023-001339
|View full text |Cite|
|
Sign up to set email alerts
|

Reaching back to enhance the future: the American Association for the Surgery of Trauma Diversity, Equity and Inclusion Pipeline Program

Bethany Lauren Strong,
Latoya Silverton,
William Wical
et al.

Abstract: ObjectivesThere are significant disparities in the surgical workforce in comparison with medical student demographics. Pipeline programs have shown to be effective in addressing gaps. The American Association for the Surgery of Trauma Diversity, Equity and Inclusion Committee designed a longitudinal pipeline program with high school student mentees and surgeon mentors providing an in-person hands-on workshop.MethodsThe mentee demographics and socioeconomic status at the time of application were determined usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…1 2 Strong et al examined the impact of a pathway program, established by the American Association for the Surgery of Trauma (AAST) Diversity, Equity, and Inclusion (DEI) Committee, on high school (HS) students with healthcare career interests. 3 We applaud the authors for implementing and evaluating a pathway program to improve diversity in surgery.The study identified 10 HS students, primarily from a medical career exposure program at the University of Chicago and assigned them to faculty mentors with similar backgrounds (eg, gender, racial and ethnic concordance). Students were expected to meet four times virtually, or in-person, during an academic year and to attend a workshop held at the AAST annual meeting.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 2 Strong et al examined the impact of a pathway program, established by the American Association for the Surgery of Trauma (AAST) Diversity, Equity, and Inclusion (DEI) Committee, on high school (HS) students with healthcare career interests. 3 We applaud the authors for implementing and evaluating a pathway program to improve diversity in surgery.The study identified 10 HS students, primarily from a medical career exposure program at the University of Chicago and assigned them to faculty mentors with similar backgrounds (eg, gender, racial and ethnic concordance). Students were expected to meet four times virtually, or in-person, during an academic year and to attend a workshop held at the AAST annual meeting.…”
mentioning
confidence: 99%
“… 1 2 Strong et al examined the impact of a pathway program, established by the American Association for the Surgery of Trauma (AAST) Diversity, Equity, and Inclusion (DEI) Committee, on high school (HS) students with healthcare career interests. 3 We applaud the authors for implementing and evaluating a pathway program to improve diversity in surgery.…”
mentioning
confidence: 99%